Effects of Exercise on Parkinson’s Disease: A Meta-Analysis of Brain Imaging Studies - Li, Jingwen; Guo, Jian; Sun, Weijuan; Mei, Jinjin; Wang, Yiying; Zhang, Lihong; Zhang, Jianyun; Gao, Jing; Su, Kaiqi; Lv, Zhuan; Feng, Xiaodong; Li, Ruiqing (Frontiers in Human Neuroscience, 2022)
Background: Exercise is increasingly recognised a key component of Parkinson’s disease (PD) treatment strategies, but the underlying mechanism of how exercise affects PD is not yet fully understood. Objective: The activation likelihood estimation (ALE) method is used to study the mechanism of exercise affecting PD, providing a theoretical basis for studying exercise and PD, and promoting the health of patients with PD. Methods: Relevant keywords were searched on the PubMed, Cochrane Library, and Web of Science databases. Seven articles were finally included according to the screening criteria, with a total sample size of 97 individuals. Using the GingerALE 3.0.2 software, an ALE meta-analysis was performed using seven studies that met the requirements and the probability of each voxelʼs cross-experiment activation was calculated. Results: The meta-analysis produced seven clusters, and major activations were found in the cerebellum, occipital lobe, parietal lobe, and frontal lobe brain regions. Conclusion: Exercise for PD mainly results in enhanced activation of the cerebellum, occipital lobe, parietal lobe, and frontal lobe. Exercise for PD does not cause a change in the activation of a single brain area, and the observed improvement may result from coordinated changes in multiple brain areas.